(g * f) (3) = 2
Explanation:
- Here, it is asked us to find the function of a function, where f(x) and g(x) are two different functions, we are asked to solve the combined equation of these two functions.
- For these, first we need to find g(f(x)) then you can find the answer for the given equations
- g ( f(x) ) = g (V), it is given that f(x) = V, so we just substituted in f(x) position.
Now, we need to (g (V)) (3) =
![V^(2) - 7 = 3^(2) - 7 = 9 - 7 = 2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/yybz3pnvw5rypiaebdw2g856qubl0d0617.png)
Hence, the answer to function of function is 2